(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Anthropomorphic metaphors, which attribute human characteristics to non-human entities, play a significant role in shaping language and culture. This article explores the similarities and differences in the use of anthropomorphic metaphors in English and Uzbek, analyzing their linguistic, cultural, and cognitive aspects. By examining examples from both languages, we aim to uncover the underlying cultural values and conceptual frameworks that influence metaphorical expressions.